1995
DOI: 10.1007/bf01454012
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical localization of heart-type fatty-acid binding protein in human and murine tissues

Abstract: A b s tra c t C ellular fatty acid-binding proteins (FABP) are a highly conserved fam ily of proteins consisting o f several subtypes» am ong them the m am m ary-derived growth inhibitor (M D G I) w hich is quite hom ologous to or even identical with the heart-type FABP (H-FABP). The FABPs and M D G I have been suggested to be in volved in intracellular fatty acid m etabolism and traffick ing. Recently, evidence for grow th and differentiation regulating properties of M D G I and H -FA B P was provid ed. U sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 57 publications
5
31
0
Order By: Relevance
“…The developmental profile of Fabp3 expression was consistent with this protein mostly localizing in Leydig cells (Heuckeroth et al 1987, Watanabe et al 1991, Zschiesche et al 1995 and with the fact that intratesticular testosterone concentrations (O'Shaughnessy et al 2002), as did Fabp3 (present results), showed a decline between P10 and P20, followed by an increase at P25. We confirmed that FABP3 protein was interstitially located and that it displayed low signal level at P6, decreased at P18, and was plentiful in adult testis (see Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The developmental profile of Fabp3 expression was consistent with this protein mostly localizing in Leydig cells (Heuckeroth et al 1987, Watanabe et al 1991, Zschiesche et al 1995 and with the fact that intratesticular testosterone concentrations (O'Shaughnessy et al 2002), as did Fabp3 (present results), showed a decline between P10 and P20, followed by an increase at P25. We confirmed that FABP3 protein was interstitially located and that it displayed low signal level at P6, decreased at P18, and was plentiful in adult testis (see Fig.…”
Section: Discussionsupporting
confidence: 89%
“…H-FABP was first shown to be released from injured myocardium in 1988, after which several studies investigated its application as a biochemical marker of myocardial injury. The H-FABP isoform is produced not only in cardiomyocytes but also, to a lesser extent, in skeletal muscle (23 ), distal tubular cells of the kidney (24 ), specific parts of the brain (25 ), lactating mammary glands, and placenta (23 ). Human H-FABP contains 132 amino acid residues and is an acidic protein (pI 5) (26 ).…”
Section: H-fabp Physiologymentioning
confidence: 99%
“…In patients treated with standard thrombolytic therapy after AMI, plasma concentrations of H-FABP and myoglobin peaked at ϳ4 h after first symptoms, whereas creatine kinase (creatine phosphokinase or CK-MB) and lactate dehydrogenase peaked at ϳ12 and 20 h, respectively (52 ). Because H-FABP and myoglobin rapidly return to their respective URLs (within 24 h after AMI) as a result of renal clearance (23,52 ), both proteins can be used to assess a recurrent infarction within 10 h after first AMI (58 ), which might be missed by CK-MB, cTnT, and cTnI because plasma concentrations of these markers return much more slowly to reference (62 ). These differences in release kinetics do not impact the measurement of cardiac proteins in plasma, however (32,58,62 ).…”
Section: Clinical Interpretation Of Plasma H-fabp Concentrationsmentioning
confidence: 99%
“…Furthermore, blocking antibody for MRG/B-FABP can block glial cell differentiation (31). MDGI/H-FABP protein has been detected mainly in myocardium, skeletal and smooth muscle fibers, lipid and steroidsynthesizing cells of adrenals, lactating mammary gland, and terminally differentiated epithelia of the respiratory, intestinal, and urogenital tracts (6). The results provide evidence that expression of MDGI is associated with an irreversibly postmitotic and terminally differentiated status of cells.…”
Section: Discussionmentioning
confidence: 82%